Substitution dependent multi-color AIE behavior and ESIPT active A-D-A type triphenylamine supported bis unsymmetrical azine derivatives and their antibacterial activity. (July 2022) - Mathivanan, Moorthy; Murugesapandian, Balasubramanian
Abstract: A facile synthetic approach afforded a new family of AIE active and ESIPT featured A-D-A (Acceptor-Donor-Acceptor) type symmetrical triphenylamine centered bis unsymmetrical azine derivatives TPSA, TPHY, TPDS and TPOV . Depending upon the substituent in the periphery, all compounds displayed frail fluorescence in the solution state and exhibited strong multi-color luminescence character in aggregated/solid state. The results achieved from UV–visible absorption, emission and theoretical studies confirmed the existence of the intramolecular proton transfer phenomenon in the excited state (ESIPT). The experimental results affirmed AIE behavior present in the compounds and it might be due to the restriction of the intramolecular rotation (RIR) mechanism. The in vitro antibacterial activity of the compounds was also scrutinized against elected bacterial strains ( B. subtilis, S. aureus, E. coli, and P. aeruginosa ) in different concentrations (0.5 mM, 1 mM, 1.5 mM). The results revealed that all four compounds have excellent antibacterial activity at 1.5 mM than other concentrations tested in the present study. Further, the fluorescence feature of the compounds was explored via fluorescence microscopy to probe the microbes ( Pseudomonas aeruginosa ). Highlights: A new A-D-A type symmetrical triphenylamine centered bis unsymmetrical azine family was developed. All compounds exhibit aggregation induced emission behavior in THF-water mixture. All compounds show solvent dependent optical responses and ESIPT phenomenon. The in vitro antibacterial activity of all compounds were established. Fluorescence feature of the compounds were explored in Pseudomonas aeruginosa via fluorescence microscopy.